(untitled) (BIRDEM Medical Journal, 2020)
Background: Routine use of diagnostic laparoscopy for the evaluation of all cases of female infertility is under debate. Until now, laparoscopy has been widely used as a diagnostic and therapeutic means of treating infertility. This study investigates the fertility outcome for women 2 to 3 years after laparoscopic management. It assessed the benefit and effectiveness of both diagnostic and laparoscopic ovarian drilling regarding reproductive outcome and menstrual regularity. Methods: From May 2013 to November 2014, a total of 303 infertile women undergoing laparoscopy at BIRDEM Hospital, were asked to participate in the study. Sixty subjects were lost to follow up making the study sample size 243. Results: Mean age at the time of laparoscopy was 29.86 ± 4.6 (range 21 - 43) years, 61.7% of women (150 cases) were nulliparous, 38.3% (93 cases) had one child, abortion or ectopic pregnancy. From the time of index surgery to follow-up, 40.3% (98) of women who had tried to conceive had home pregnancy test positive and 25.5% (62) had a live birth following their surgery. Among these 62 subjects, 33 underwent Laparoscopic Ovarian Drilling (LOD) and other 29 had diagnostic laparoscopy along with or without other laparoscopic manipulations. A Chi-square test has revealed that there was significant increase in regularization of menstrual cycle among irregularly menstruating women after laparoscopy indicating regular ovulatory cycles. Conclusion: Laparoscopic procedures can lead to positive results while treating infertility as well as menstrual disturbances, thus establishing a defined position in current fertility practice. Birdem Med J 2020; 10(2): 125-129